Diagnosis strategy of adipocytic soft-tissue tumors in adults: a consensus from European experts - Moulin, Benjamin; Messiou, Christina; Crombe, Amandine; Kind, Michèle; Hohenberger, Peter; Rutkowski, Piotr; van Houdt, Winan J.; Strauss, Dirk; Gronchi, Alessandro; Bonvalot, Sylvie (European journal of surgical oncology, 2022)
Fat-containing tumors are very commonly found in daily practice with benign lipoma accounting for the majority of superficial tumors. Overlap in imaging findings between benign and intermediate or malignant fat-containing tumor is common. Guidelines recommend a core needle biopsy (CNB) for all deep tumors, and superficial tumors over 3 cm. However, specific strategy for diagnosis and referral to a sarcoma center should be applied on adipocytic tumors. The aim of this consensus statement is to provide a specific algorithm for adipocytic tumors, to discriminate patients who do require a CNB for preoperative diagnosis from those who can simply undergo active surveillance or a simple excision.